The Influence of Parenting Patterns on Learning Interests of Class II MI Islamiyah Sumberwudi Students - Siti Hartina Suryani; Widiyah Natalia; Amiriana Biverlia Nova; Wafida Halimatuz Zuhriah (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Parenting is the entire treatment of parents that is applied to children. At MI Islamiyah Sumberwudi, parents face several obstacles in giving attention to children, including limited costs so that they prioritize work, lack of time with children, and a lack of understanding of parents in parenting their children properly in carrying out tutoring. Some believe that when a child is sent to school, the parent's duty to educate their children is released. This study aimed to determine the effect of parenting style on the learning interest of class II students at MI Islamiyah Sumberwudi. This study uses a quantitative approach with a correlational type. The method used is observation, interviews, questionnaires, and documentation. Data analysis used a normality test, simple linear regression test (simple regression correlation test, correlation coefficient test, determinant coefficient test, t-test), and hypothesis t-test. The study's findings indicated that class II pupils at MI Islamiyah Sumberwudi's parenting style impacted their enthusiasm for learning. Strength was rated as